Transcriptome Analysis and Single-Cell Sequencing Analysis Constructed the Ubiquitination-Related Signature in Glioma and Identified USP4 as a Novel Biomarker - Tang, Qikai; Chen, Zhengxin; Xie, Jiaheng; Mo, Chuangqi; Lu, Jiacheng; Zhang, Qixiang; Wang, Zhangjie; Wu, Wei; Wang, Huibo (Frontiers in Immunology, 2022)
Background Glioma, the most frequent malignant tumor of the neurological system, has a poor prognosis and treatment problems. Glioma’s tumor microenvironment is also little known. Methods We downloaded glioma data from the TCGA database. The patients in the TCGA database were split into two groups, one for training and the other for validation. The ubiquitination genes were then evaluated in glioma using COX and Lasso regression to create a ubiquitination-related signature. We assessed the signature’s predictive usefulness and role in the immune microenvironment after it was generated. Finally, in vitro experiment were utilized to check the expression and function of the signature’s key gene, USP4. Results This signature can be used to categorize glioma patients. Glioma patients can be separated into high-risk and low-risk groups in both the training and validation cohorts, with the high-risk group having a significantly worse prognosis (P<0.05). Following further investigation of the immune microenvironment, it was discovered that this risk grouping could serve as a guide for glioma immunotherapy. The activity, invasion and migration capacity, and colony formation ability of U87-MG and LN229 cell lines were drastically reduced after the important gene USP4 in signature was knocked down in cell tests. Overexpression of USP4 in the A172 cell line, on the other hand, greatly improved clonogenesis, activity, invasion and migration. Conclusions Our research established a foundation for understanding the role of ubiquitination genes in gliomas and identified USP4 as a possible glioma biomarker.